Evaluating the effect of fabric type on thermal insulation properties of sports clothing - Abreu, Maria José (2018)
In the present study, evaluating the fabric characteristics on thermal insulation properties of garments was aimed. For that purpose, two fiber combinations and seven different knitting structures were chosen and seven long sleeve basic shirts were manufactured from these fabrics. As a water-repellent finishing treatment, all shirts were treated with 5% of a fluorocarbon-based product. A thermal manikin of PT-Teknik made in Denmark was used to measure the heat loss of the shirts and the surface of manikin was kept at a constant temperature. Afterwards, the total and effective clothing insulation values were calculated for each shirt. The comparisons of heat loss values according to the body parts, and also for the effective clothing insulations were done. Moreover, the heat flux according to the body parts were determined. In the light of these obtained data, a new shirt design was designed and proposed by combining the evaluated fabrics in order to enhance the comfort and performance of the user.